VOLATILITY OF EXCHANGE RATE EFECTING TRADE GROWTH- A CASE OF PAKISTAN WITH US, UK AND UAE - Marria Hassan (European Scientific Journal, ESJ, 2013)
Primary objective of this paper is to investigate fluctuations in trade of Pakistan resulting from volatility in exchange rate of three of the major trading partners including United States of America, United Kingdom, and the United Arab Emirates. This paper covers a longer period of time from 1988:8 to 2011:6 using monthly data. ADF is used to check stationarity of the variables, Garch estimates volatility of exchange rate, co-integration measures long run relationship, VECM estimates adjustment in trade growth in short run due to change in exchange rate. Empirical results show a negative effect between trade growth and exchange rate.